Dietary Aroclor 1254-Induced Toxicity on Antioxidant Capacity, Immunity and Energy Metabolism in Chinese Mitten Crab Eriocheir sinensis: Amelioration by Vitamin A - Feng, Dexiang; Wang, Xiaodan; Li, Erchao; Bu, Xianyong; Qiao, Fang; Qin, Jianguang; Chen, Liqiao (Frontiers in Physiology, 2019)
Effects of dietary PCB exposure and dietary vitamin A supplementation on E. sinensis were studied with the aim to explain dietary PCB toxicity and toxic alleviation by vitamin A intake in crab. Four diets were used including three experimental diets containing 0, 80000 or 240000 IU/kg vitamin A with each experimental diet containing 10 mg PCB/kg diet, and a control diet (without vitamin A and PCB supplementation) in an 8-week feeding trial. Crabs fed the PCB-only diet had significantly lower weight gain than those fed the control diet. No significant difference was observed in crab survival among all groups. Crabs fed the PCB-only diet had a significantly higher malondialdehyde content and antioxidase superoxide dismutase activity in the serum and hepatopancreas, and higher erythromycin N-demethylase and glutathione S-transferase activities in the hepatopancreas than those fed the control diet. However, supplementation of dietary vitamin A decreased the levels of all these parameters. The hepatopancreatic cytochrome P450 2 and 4 (CYP2, CYP4), fatty acid binding proteins 3 and 10 (FABP3, FABP10) and IL mRNA levels in the PCB-only group were significantly higher than those in the control group, and dietary 240000 IU/kg vitamin A supplementation decreased hepatopancreatic CYP4, FABP3, FABP10 and intracellular lipolytic enzyme mRNA level. The crab fed PVA80K had the highest level of retinoid X receptor mRNA in the hepatopancreas. The structure of the hepatopancreas was damaged and the deposit of lipid droplets decreased with dietary PCB exposure. Both levels of vitamin A supplementation alleviated the damage and increased lipid droplets in the hepatopancreas. Dietary PCB exposure significantly reduced total hemocyte count (THC), and phenoloxidase, acid phosphatase, lysozyme activity activities in the serum. Post-challenge survival of crab in the experimental PCB-only diet group was low compared with that in the control. Supplementation of 240000 IU/kg vitamin A significantly increased the THC and phenoloxidase activity in the serum and post-challenge survival compared with those in the PCB-only group. This study indicates that dietary vitamin A can improve the growth, antioxidant capacity, immune response, detoxification enzymes activities, energy metabolism and hepatopancreas tissue structure of Chinese mitten crab fed PCB contaminated diets.